Abordagens de avaliação educacional: a constituição do campo teórico no cenário internacional (Educational evaluation approaches: constitution of the theoretical field in the international scenario) - Borges, Regilson Maciel; Rothen, José Carlos (Revista Eletrônica de Educação, 2019)
This article presents a theoretical review of the main evaluation approaches that marked the trajectory of educational evaluation in the international scenario. This is a bibliographical research that, based on the assessment literature, aimed at studying the various dimensions and different meanings that have historically constituted the educational evaluation field. Seven evaluation approaches are described: goal-based evaluation, evaluation based on scientific logic, value-based evaluation, decision-making evaluation, consumer-oriented evaluation, participant-centered evaluation, and qualitative evaluation. Each one of them is characterized according to its protagonists, objectives, conceptual approaches, theoretical orientations deriving from methodological assumptions, and the scholars who continued their respective approaches. Such international literature had a strong influence on Brazilian evaluation researchers who, based on these references, sought to support a field of knowledge that is still in the process of constitution and strengthening in our country. Resumo Este artigo apresenta uma revisão teórica das principais abordagens de avaliação que marcaram a trajetória da avaliação educacional no cenário internacional. Trata-se de uma pesquisa bibliográfica que, referenciada na literatura da avaliação, busca estudar as variadas dimensões e os diferentes sentidos que constituíram historicamente o campo da avaliação educacional. São descritas sete abordagens de avaliação: a avaliação baseada em objetivos, a avaliação baseada na lógica científica, a avaliação baseada no valor agregado, a avaliação a serviço da decisão, a avaliação orientada para consumidores, a avaliação centrada nos participantes e a avaliação qualitativa. Cada uma dessas abordagens é caracterizada segundo seus protagonistas, objetivos, enfoques conceituais, orientações teóricas decorrentes de pressupostos metodológicos e os estudiosos que deram continuidade nas suas respectivas abordagens. Essa literatura internacional exerceu forte influência sobre os pesquisadores brasileiros da avaliação que, fundamentados nesses referenciais, buscaram sustentar uma área de conhecimento que ainda se encontra em processo de constituição e fortalecimento em nosso país. Keywords: Educational evaluation, Evaluation approaches, Theories on evaluation. Palavras-chave: Avaliação educacional, Abordagens de avaliação, Teorias em avaliação. References ALKIN, Marvin C.; CHRISTIE, Christina A. An evaluation theory tree. In: ALKIN, Marvin C. (Ed.). Evaluation roots: tracing theorists’ views and influences. London: Sage, 2004. p. 381-392. CAMPBELL, Donald T.; STANLEY, Julian C. Experimental and quasi-experimental designs for research on teaching. In: GAGE, N. L. (Ed.). Handbook of research on training. Chicago: Rand McNally, 1963. p. 1-84. DE KETELE, Jean-Marie. L’évaluation conjuguée en paradigmes. Revue Française de Pédagogie, Lyon, n. 103, p. 59-80, 1993. DIAS SOBRINHO, José. Campo e caminhos da avaliação: a avaliação da educação superior no Brasil. In: FREITAS, Luiz Carlos (Org.). Avaliação: construindo o campo e a crítica. Florianópolis: Insular, 2002. p. 13-62. FERNANDES, Domingos. Acerca da articulação de perspectivas e da construção teórica em avaliação educacional. In: ESTEBAN, Maria Teresa; AFONSO, Almerindo Janela (Orgs.). Olhares e interfaces: reflexões críticas sobre a avaliação. São Paulo: Cortez, 2010. p. 15-44. GUBA, Egon G.; LINCOLN, Yvonna S. Avaliação de quarta geração. Trad. Beth Honorato. Campinas: Editora da Unicamp, 2011. HOUSE, Ernest; HOWE, Kenneth R. Deliberative democratic evaluation in practice. In: STUFFLEBEAM, Daniel L.; MADAUS, George F.; KELLAGHAN, Thomas (Eds.). Evaluation models: viewpoints on educational and human services evaluation. Boston: Kluwer Academic Publishers, 2000. p. 409-422. MACDONALD, Barry. Uma classificação política dos estudos avaliativos. In: GOLDBERG, Maria Amélia Azevedo; SOUSA, Clarilza Prado de (Orgs.). Avaliação de programas educacionais: vicissitudes, controvérsias, desafios. São Paulo: EPU, 1982. p. 16-17. OWSTON, Ron. Models and Methods for Evaluation. In: SPECTOR, J. Michael et al. (Eds.). Handbook of Research on Educational Communications and Technology. New York: Lawrence Erlbaum Associates, 2008. p. 605-618. PARLETT, Malcolm; HAMILTON, David. Avaliação Iluminativa: uma nova abordagem no estudo de programas inovadores. In: GOLDBERG, Maria Amélia Azevedo; SOUSA, Clarilza Prado de (Orgs.). Avaliação de programas educacionais: vicissitudes, controvérsias, desafios. São Paulo: EPU, 1982. p. 38-45. SANDERS, William L.; HORN, Sandra P. The Tennessee value-added assessment system (TVAAS): mixed model methodology in educational assessment. Journal of Personnel Evaluation in Education, New York, v. 8, n. 3, p. 299-311, 1994. SANDERS, William L.; RIVERS, June C. Cumulative and residual effects of teachers on future student academic achievement. Knoxville: University of Tennessee Value-Added Research and Assessment Center, 1996. STAKE, Robert E. Evaluation the arts in education: a responsive approach. Columbus: Merril, 1975a. STAKE, Robert E. Program evaluation, particularly responsive evaluation. Kalamazoo: Western Michigan University Evaluation Center, 1975b. (Occasional paper n. 5). STUFFLEBEAM, Daniel L. Evaluation models. New directions for evaluation, San Francisco, n. 89, p. 7-98, 2001. STUFFLEBEAM, Daniel L.; SHINKFIELD, Anthony L. Evaluación sistemática: guía teórica y práctica. Trad. Carlos Losilla. Barcelona: Paidós, 1987. WORTHEN, Blaine R.; SANDERS, James S.; FITZPATRICK, Jody L. Avaliação de programas: concepções e práticas. Trad. Dinah de Abreu Azevedo. São Paulo: Gente, 2004.